The Impact of Strategic Management Accounting Techniques on the Reliability of Financial Statements:: The Impact of Strategic Management Accounting Techniques on the Reliability of Financial Statements: (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The objective that the researcher seeks to achieve through this research is to clarify the relationship between strategic management accounting techniques and the reliability of financial statements, and to measure the impact of these techniques as an independent variable with its three dimensions, which are: activities-based cost, target cost, and benchmarking on the reliability of financial statements as a dependent variable. To achieve this objective, the researcher did the following: First: Determine the research problem through the following question: Do strategic management accounting techniques affect the reliability of financial statements in industrial companies listed on the Palestine Exchange? Second: Making the analytical descriptive approach adopted in this research; Third: Employing the questionnaire as the primary method for obtaining data from the study sample of workers in the aforementioned companies, numbering (52) respondents. Fourth: Analyzing the data based on the statistical program (SPSS) to find: (arithmetic average, standard deviation, relative weight, coefficient of variation, correlation coefficient, T-test, regression analysis, F test, and coefficient of determination), through this research, the researcher has reached several important results, the most important of which is that the reliability of the data is affected by strategic management accounting techniques in a substantial and statistically significant way.